"You must leave but I didn't want to leave": qualitative evaluation of the integration of ART into postnatal maternal and child health services in Cape Town, South Africa. Issue 4 (2nd April 2020) - Pellowski, Jennifer A.; Weber, Alison Z.; Phillips, Tamsin K.; Brittain, Kirsty; Zerbe, Allison; Abrams, Elaine J.; Myer, Landon
ABSTRACT: Postpartum HIV care retention rates are well below retention rates of the general adult population. The Maternal-Child Health Antiretroviral Therapy (MCH-ART) trial tested the benefit of integrating postpartum maternal ART and pediatric care through the end of breastfeeding compared to the standard of care of immediate postpartum referral of mother and infant to separate services. After the trial, twenty-one participants completed in-depth interviews to understand the acceptability of the service integration and the potentially differing "lived" experiences of the women randomized to the two conditions. Key findings include: (1) the MCH-ART integrated service was found to be acceptable, (2) women in the intervention condition expressed more negative feelings around the need to be transferred to general ART services and (3) women in the intervention condition perceived that they had more influence in selecting the clinic to which they would be transferred compared to those in the control group, although there was no actual difference by study design. Future work should more directly evaluate the impact of shared decision-making and long-term relationships with clinic staff on patient engagement and retention in HIV care.